Teologie en ontologie : Oor die wetenskap as nagmerrie vir die Teologie - en omgekeerd - Schulze, L.F. (Koers, 1986)
The author argues that the Christian world view, rooted in the biblical revelation of the transcendent almighty God, is incompatible with the currently still popular concept of science, which presupposes a world view whose roots lie embedded in Greek ontology. Tracing the prominent role of determinism as embodied in the concept of Anangké in Greek ontology, it is shown that A ristotle's breakthrough in acknowledging change and teleology was mere appearance and that his world view was still enchained to the determinism of traditional ontology. It was Duns Scotus who exposed the determinism inherent in A ristotle's System and who broke free from these schackles by conceding the p ossibility of synchronic contingency. The medieval absorption of Greek ontology into Christianity firmly entrenched Greek notions in Western thought. Con sequently science viewed creation as a closed, causally determined system. While modern physics has opened up a new vision of the universe, the traditional (outmoded) "scientific" outlook is rampant and many of its presuppositions and models are projected on theology in order to safe guard theology's "scientific" character. In this way theology largely forfeits its true task.